A noção de interesse na escola nova: formulações teóricas e a interpretação de Anísio Teixeira de 1924 a 1932 - Sergio Tulio Generoso de Mattos (2008)
The present study aims to argue the notion of interest in the educational thought of Anísio Teixeira (1900 1971). Anísio Teixeira is considered by many scholars one of the major contributors to bring the American philosopher and educator John Deweys theoretical formulations to Brazil. Despite this, Anísio Teixeiras educational thought cannot be reduced to only the North American influence, for before it, Teixeira would have also been influenced by the European educational thought. In our trials, we noticed that little had been studied about the period when Teixeira goes between these two influences, particularly regarding the notion of interest and its relatedness to the notion of freedom. In 1932, Teixeira denounces an unsuitable application of the modern education theory, which would have led to a misconstruction of the New School. This was the main motivation in our study and, on the other hand, the final milestone of our researches, since we attempted to understand the causes and origins of such denunciation. Throughout the development of our researches, we could identify that much of what happened to Teixeira would not have been possible if he had not taken over the position of General Teaching Inspector of Bahia in 1924, which happened to constitute our initial milestone. In such period, despite the European influences, Teixeira blatantly takes the North American influences, especially those of John Deweys and William Kilpatricks. However, as we studied Dewey more deeply, we realized that, in spite of his formulation originality, he had Johann Herbarts and William Harriss theories opposition to each other, the theories of interest and of effort respectively, as the framework of his thought. Regarding the European influences, we noticed, sometimes explicitly sometimes not, a great dialogue between Teixeira and the theoretical formulations of Ovídio Decroly, Maria Montessori and Edouard Claparède, which made us dedicate part of our study to them. If many are the conceptions of interest, etimologically, the word interest is constituted of the latin preposition inter, that means between, and est (esse), which designates people, things and facts of the world. In other words, interest is what can be raised in the relationship between the people and the things in the world. At the end of this work, it was possible to conclude that the notion of interest in Anísio Teixeira had not been limited to a reproduction of the deweyan ideas, since he had also been inspired by educational thoughts of Europe, which made him go beyond Dewey.